Métodos preventivos em primeiro molar permanente de crianças com experiência de cárie dentária: estudo clínico comparativo - Oliveira, Daniela Cristina de [UNESP] (2015)
It is in childhood that the teeth in general, are more vulnerable, are more susceptible to getting tooth decay, especially in the outbreak period, hampering their proper hygiene. Also, it is added to the little child's ability to perform the maneuvers of proper tooth brushing. The first permanent molar eruption, in addition to cited susceptibility factors, is par excellence a microorganism colonization niche because of its occlusal anatomy, a fact that makes of this period highly risky for the emergence of new lesions of dental caries. Therefore, based on the premise that children with caries experience in the permanent molar eruption phase are more likely to acquire the disease, the goal of this study was to compare three preventive methods of occurrence of carious lesions in the tooth. The study included 242 children (968 molars), of both genders, aged 6-8 years, with caries experience, with the four first permanent molars at the erupting phase. The children were randomly divided into three groups: a group of 81 children, whose 324 molar received a single application of pit and fissure sealant made on the basis of glass ionomer (GIS), a group of 83 children (332 molars), with coating application of fluoride varnish (FV) in 3 sessions (0, 6 and 12 months) and a group of 78 children (312 molars) who received professional prophylaxis (PP) in 6 sessions (0, 3, 6, 9, 12 and 15 months). Patients were clinically evaluated after 6, 12 and 18 months, patients...